The rise of multimodality : applying translation criticism to video games - Sönmez, Mehmet Eren. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis explores how the video game The Witcher 3: Wild Hunt (W3WH) and its official translation alongside a fan translation into Turkish can be systematically analyzed by a translation criticism model. The study also focuses on how the recent rise of multimodality within Translation Studies can offer new perspectives in the way translation is viewed. Based on the literature on video game translation practices, this study carries out a discussion on the terminology used to describe such practices, analyzing the variety in the use of terms from the perspective of the expanding research area of Translation Studies. By investigating the two translations of the video game W3WH, the study aims to find out the differences in translation strategies between the official translation and the fan translation. The study also discusses the choice of fan translators to continue with their translation process despite the launch of the official translation. Moreover, the industry’s reduced view of translation is challenged, in contrast with localization and transcreation. Within this frame, the study relies on a critical analysis that integrates the different modes and assets in the video game to draw a comprehensive picture of the gameplay experience. The thesis hopes to increase the cooperation between academia and industry by promoting a bidirectional learning process.
Keywords: Video games -- Terminology -- Translating.; Audio-visual translation.